(1/3a^2b-1/6ab)/( )=3ab
2个回答
1/3a^2b-1/6ab
=1/3ab(a-1/2)
=3ab(a/9-1/18)
(1/3a^2b-1/6ab)/(a/9-1/18 )=3a
相关问题
①(-3ab)(2a^b+ab-1)②(6ab^3+2ab^2-3ab+1)(-2a^b)
6ab-3【3b^2-(a^2-2ab)+1] a=-2 b=-1/3
1/3ab(2a^2-ab+6b^2)
计算:(1)a^-2b^-3·(-3a^-1b^2)÷6a^-4b^-2 (2)(3ab)^-3(2ab^-1)^-2
3(a³-a²+1/2ab²)-1/2(6a³+4a²b+3ab&su
已知a+b=1,ab=-2求-(2ab-6a-2a)-3(ab+1/3a-b)的值
计算 (a^2b-ab-a+1)/(ab^2+3ab-b-3)÷(a^2+a_2)/(b^2+b-6)
已知a+b=1,ab=-2,求代数式-(2ab-6a-2b)-3(ab+1/3a-b)的值
第1题 (2a-3b)(3b+2a)-(8a^3b-6ab^3)/2ab=
化简求值 ab^3+a^2b^3+2-2ab+3ab^3-a^2b^3+2ab-1,a=1,b=-1